Penyelesaian Konflik Agraria Dengan Skema Hutan Kemasyarakatan di Kecamatan Bukit Kapur - Anshori, M Wira; Syahrier, Fajar Alan; Ahmad, Zakly Hanafi; Pratama, Galank; Sazeta, Mirza; Romadhon, Aditya (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Riau, 2025)
Agrarian conflict is a recurring structural issue in Indonesia, mainly caused by overlapping land claims and legal uncertainty. This study examines the conflict in Bagan Besar, Dumai, focusing on key actors, root causes, and resolution mechanisms. Using a qualitative approach through document analysis, interviews, and field observations, the research finds that the Community Forest (HKm) scheme serves as a legal tool to secure land tenure and foster multi-stakeholder collaboration. HKm also enables the transition of encroachers into government partners in sustainable forest management. Nevertheless, challenges persist, such as mechanized land encroachment and weak institutional legitimacy. The success of HKm implementation relies on coherent government policies and active community participation in building inclusive and sustainable forest governance.